PENERAPAN TEORI BELAJAR VAN HIELE PADA MATERI GEOMETRI DI KELAS VIII - Beni Junedi (Universitas Islam Sumatera Utara, 2017)
This article discussed about theory applaying learning according Van Hiele is learning that focus on Geometry. This theory is found that to study Geometry the student have a development to think step by step certain. The steps student cognitive level consist of 1) Visualisation level is introducing level, 2) Analisys level is description level, 3) Abstraction level (deduction informal) is arraged level or relational level, 4) Deduction formal level, and 5) Rigor level is systhematys level. This implementation in the class Van Hiele determine some of learing faces 1) Information is about question answer for introducing the student, 2) Direction method is about the students to know the topic that have been learned by tools with accorate that have prepared the teacher make some observation, 3) Explication is explain a view appear about structure that have observation, 4) Free orientation is how the students faced task more than a way and task open ended and fase and 5) Integration is the students observe review and resume that have learn. Study applying theory Van Hiele more than applying on student activity, because student activity is role important on the procees of learning used study applying theory.